Projetos de trabalho e educomunicação: possíveis contribuições no ensino fundamental - Santos, Gilmara Ozorio da Silva (2017)
Currently, the role that communication plays in education is complex and has undergone a wide process of transformation, in a way that fosters theoretical and practical advances around the educational environment. From this point of view, the view of scholars turned to the interface between Communication and Education has grown gradually. Given this approach, it is believed that the Educommunication, together with the Work Projects perspective, may contribute to strengthen the communicative ecosystem in the school, in order to rescue the center of interest of the classes and promote the youth protagonism of the students. Thus, the present research, developed in the Graduate Program in Communication and Society, in the Interdisciplinary Professional Master's Degree in Technologies, Communication and Education of UFU, aims to analyze the possible conceptual and practical contributions of the encounter between Educommunication and the Work Projects for teaching pedagogical practice in elementary school. This perspective unfolds in: deepening the concept and foundations of Educommunication, presenting the dialogue between communication and education; investigating the theoretical and methodological assumptions of the Work Projects as a possibility to (re) signify the teaching pedagogical practice and to delineate a meeting point between Educommunication and Work Projects to structure propositive actions from Educomunicative Projects destined to the teachers working at this level of education. The theoretical contribution on Educommunication was traced by authors such as Soares (2011); Citelli, (2004); Martín-Barbero (2005); Kaplún (1999); Orozco Gómez (2014); Aparici (2014) and Ângela Schaun (2002). For the Work Projects axis the study took place in the light of Dewey (1979); Hernández (1998); Leite, Oliveira and Maldonado (1998). As for the methodological procedures, the assumptions of the qualitative approach were chosen. The trajectory of the study was based on applied research of the exploratory type and the data were obtained through the bibliographic survey. Aligned with the investigative course, the results indicated that there is a possibility of dialoguing teaching-learning proposals between Educommunication and Projects in the elementary school from Educomunicative Projects for the defined age group, combining the teaching work with interdisciplinary propositional actions from social intervention areas. Keywords: Work Projects. Educommunication. Educomunicative Projects. Elementary School.